Chuva branca caía em chãos de Maíconã : a trilogia de Paulo Jacob - Bentes, Arão do Nascimento (2015)
It is proposed that this work analyzing three novels of Paul Jacob (1921-2003), Amazon writer of Postmodernism. The novels are: Chãos de Maiconã,Um Pedaço de Lua Caía na Mata and Chuva Branca. Each of these works works, metonymically with population segments that feature the Amazon. At first, the author focuses on the indige-nous element, which is the autochthonous, since already inhabit the soil of the region long before the first settlers arrived here. With the second novel, the author focuses on the segment of immigrants, having given preference to Jews who played important role in the early Amazonian economy, made almost exclusively exchange products through the channel of the rivers. Finally, in White Rain, Jacob focuses on the second typical population segment forest: the caboclo riverside. The set of three narratives constitute a trilogy that gives account of the different ways of life and even of winning the Amazo-nian hinterland. As hits the analysis of the mentioned works will be focused to language employed by the narrator, which recreates the Portuguese standard, reworking the syn-tax and semantics, either as reproduction of regional dialects, whether as a literary rec-reation of our language. In addition, there is the religious, indelible feature in the narra-tive. Finally, Jacob will be framed in the historical journey of both the Brazilian litera-ture as literature just as it took place, with several peculiarities in the Amazon. Keywords: Indian, mestizo , immigrant, myth, language and Amazon.